Previous traumatic brain injury is associated with an increased odds for gestational diabetes: a nationwide register-based cohort study in finland - Vaajala, Matias; Kuitunen, Ilari; Liukkonen, Rasmus; Ponkilainen, Ville; Kekki, Maiju; Mattila, Ville M. (Acta diabetologica, 2023)
Aims Despite recent findings that traumatic brain injury (TBI) is a possible risk factor for type 2 diabetes (DM2) and that a strong association exists between gestational diabetes (GDM) and the risk for the development of DM2, no previous studies have investigated the effects of TBI on the risk for the development of GDM. Therefore, this study aims to determine the possible association between a previous traumatic brain injury and later gestational diabetes. Methods In this retrospective register-based cohort study, data from the National Medical Birth Register were combined with data from the Care Register for Health Care. Women who had sustained a TBI before pregnancy were included in the patient group. Women who had sustained previous fractures of the upper extremity, pelvis, or lower extremity were included in the control group. A logistic regression model was used to assess the risk for the development of GDM during pregnancy. Adjusted odds ratios (aOR) with 95% confidence intervals between the groups were compared. The model was adjusted by prepregnancy body mass index (BMI) and maternal age during pregnancy, the use of in vitro fertilization (IVF), maternal smoking status, and multiple pregnancies. The risk for the development of GDM during different periods following the injury (0–3 years, 3–6 years, 6–9 years, and 9+ years) was calculated. Results In total, a 75 g 2-h oral glucose tolerance test (OGTT) was performed on 6802 pregnancies of women who had sustained a TBI and on 11 717 pregnancies of women who sustained fractures of the upper extremity, pelvis, or lower extremity. Of these, 1889 (27.8%) pregnancies were diagnosed with GDM in the patient group and 3117 (26.6%) in the control group. The total odds for GDM were higher after TBI compared to the other traumas (aOR 1.14, CI 1.06–1.22). The odds were highest at 9 + years after the injury (aOR 1.22, CI 1.07–1.39). Conclusion The total odds for the development of GDM after TBI were higher when compared to the control group. Based on our findings, more research on this topic is warranted. Moreover, a history of TBI should be considered a possible risk factor for the development of GDM.